Hole transport layer, perovskite solar cell and preparation method

By adding surfactant to the self-assembled molecular layer precursor to prepare a hole transport layer, the interfacial reaction problem between the NiOx layer and the perovskite absorbing layer is solved, and the photovoltaic performance and stability of perovskite solar cells are significantly improved. sex.

CN119451386APending Publication Date: 2025-02-14TRINA SOLAR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411539750.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the interface reaction between nickel oxide (NiOx) and the perovskite absorbing layer leads to non-radiative recombination, affecting device stability and open circuit voltage, and self-assembled molecular materials have problems of uneven distribution and poor wetting. It is difficult to effectively passivate the defects at the bottom of the perovskite absorbing layer.

Method used

The self-assembled molecular layer precursor solution is added to prepare a hole transport layer, improve the interface problems between the NiOx layer and the perovskite absorbing layer, form a uniform modification layer, reduce interface defects and optimize the charge transport path.

Benefits of technology

It significantly improves the photovoltaic performance and stability of perovskite solar cells, improves the open circuit voltage and photoelectric conversion efficiency, simplifies the production process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451386A_ABST
    Figure CN119451386A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar cells, and particularly relates to a hole transport layer, a perovskite solar cell and a preparation method. The hole transport layer comprises a NiOx layer and a self-assembly molecular layer, wherein the self-assembly molecular layer comprises a self-assembly molecular material and a surfactant. The perovskite solar cell comprising the hole transport layer has the advantages of high efficiency, high stability, low production cost and simple preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solar cells, and in particular relates to a hole transport layer, a perovskite solar cell and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite solar cells (PSCs) have benefited from the advantages of high light absorption, long carrier lifetime, and high defect tolerance of their materials. The device performance has made great progress in recent years, with the highest certified power conversion efficiency (PCE) of 26.14%. Nickel oxide (NiOx) is an inorganic p-type semiconductor that is commonly used as a hole transport layer (HTL) in inverted perovskite solar cells due to its cost-effectiveness, stability, and scalability. However, the interaction between NiOx and the perovskite absorber layer can lead to interfacial reactions, resulting in non-radiative recombination at the interface, which has an adverse effect on device stability and causes open circuit voltage (VOC) loss. Commonly used self-assembled molecular materials (SAMs) are an effective way to solve the NiOx buried interface problem in inverted PSCs. However, SAMs have disadvantages such as uneven distribution and poor wettability to the perovskite precursor solution, and cannot effectively passivate the defects at the bottom of the perovskite absorber layer, which poses a major obstacle to achieving high-efficiency and high-stability inverted PSCs.

[0003] Therefore, it is urgent to develop a new interface modification method that can simplify the process, reduce costs, and improve the photovoltaic efficiency and stability of perovskite solar cells. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention proposes a method for preparing a hole transport layer by adding a surfactant to a self-assembled molecular layer precursor solution. This method improves the interface problem between the NiOx layer and the perovskite light-absorbing layer, significantly improves the photovoltaic performance and stability of the perovskite solar cell, simplifies the production process, reduces the production cost, and provides an effective solution for the performance optimization and commercial application of perovskite solar cells.

[0005] Specifically, the present invention provides a hole transport layer, which includes a NiOx layer and a self-assembled molecular layer, and the self-assembled molecular layer includes a self-assembled molecular material and a surfactant.

[0006] In one or more embodiments, the surfactant is selected from one or more of organic substances containing phosphate groups and organic substances containing phosphorylcholine groups.

[0007] In one or more embodiments, the organic substance containing a phosphate group is selected from one or more of octadecyl phosphate, dodecyl phosphate, nonylphenol polyoxyethylene phosphate, octyl polyoxyethylene phosphate, polyoxyethylene sorbitan monostearate phosphate, polyoxyethylene fatty alcohol phosphate, lecithin phosphate, triethanolamine phosphate and triethyl phosphate.

[0008] In one or more embodiments, the organic substance containing a phosphorylcholine group is selected from one or more of distearoylglycerophosphocholine, stearoylglycerophosphocholine, palmitoylglycerophosphocholine, myristoylglycerophosphocholine, laurylphosphocholine, dodecylphosphocholine, tetradecylphosphocholine, hexadecylphosphocholine, behenylphosphocholine, dilauryldimethylphosphocholine and glycerophosphocholine.

[0009] In one or more embodiments, the self-assembling molecular material is selected from one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid.

[0010] In one or more embodiments, the mass ratio of the self-assembling molecular material to the surfactant is 1:(0.001-100).

[0011] In one or more embodiments, the NiOx layer has a thickness of 1-100 nm.

[0012] In one or more embodiments, the thickness of the self-assembled molecular layer is 1-20 nm.

[0013] In one or more embodiments, the hole transport layer has a thickness of 2-120 nm.

[0014] The present invention provides a method for preparing the hole transport layer of the present invention, the method comprising: coating a self-assembled molecular layer precursor solution on the surface of a NiOx layer, and annealing to obtain the self-assembled molecular layer; the self-assembled molecular layer precursor solution comprises a self-assembled molecular material, a surfactant and a solvent.

[0015] In one or more embodiments, the NiOx layer is prepared by physical vapor deposition, spin coating, doctor blade coating or slot coating.

[0016] In one or more embodiments, the annealing temperature is 100-150°C.

[0017] In one or more embodiments, the annealing time is 5-20 min.

[0018] In one or more embodiments, the self-assembled molecular layer precursor solution is coated by spin coating, blade coating or slit coating.

[0019] In one or more embodiments, the solvent is selected from one or more of N,N-dimethylformamide, ethanol, and isopropanol.

[0020] In one or more embodiments, the concentration of the self-assembling molecular material in the self-assembling molecular layer precursor solution is 0.1-10 mg / mL

[0021] In one or more embodiments, the concentration of the surfactant in the self-assembled molecular layer precursor solution is 0.1-10 mg / mL.

[0022] In one or more embodiments, when the spin coating method is adopted, the spin coating speed is 3000-6000 revolutions per second.

[0023] In one or more embodiments, when the spin coating method is used, the spin coating acceleration is 1000-5000 revolutions per second.

[0024] In one or more embodiments, when the spin coating method is adopted, the spin coating time is 20-60 seconds.

[0025] In one or more embodiments, when the knife coating method is used, the coating speed is 5-20 mm / s.

[0026] In one or more embodiments, when the slot coating method is used, the coating speed is 5-20 mm / s.

[0027] The present invention provides a perovskite solar cell comprising the hole transport layer of the present invention.

[0028] In one or more embodiments, the perovskite solar cell further comprises a perovskite light absorbing layer on the surface of the self-assembled molecular layer of the hole transport layer.

[0029] In one or more embodiments, the perovskite light-absorbing layer comprises a perovskite structure material, the chemical formula of the perovskite structure material is ABX3, A is a monovalent cation selected from one or more of methylamine, formamidine, acetamidine, cesium and rubidium; B is a divalent metal cation selected from one or more of lead, tin, copper and germanium; X is a monovalent anion selected from F - ,I - Br - , Cl - 、BF4 - PF6 - and SCN - One or more of . BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the structure of perovskite solar cells prepared according to some embodiments of the present invention. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.

[0032] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0033] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0034] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0035] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0036] Herein, when describing embodiments or examples, it should be understood that it is not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined herein.

[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0038] The hole transport layer provided by the present invention comprises a NiOx layer and a self-assembled molecular layer, wherein the self-assembled molecular layer may comprise a self-assembled molecular material and a surfactant. In the present invention, the addition of a surfactant allows the solution to have better wettability, can form a uniform modified layer on the NiOx layer, effectively reduces interface defects, improves the interface characteristics between NiOx and the perovskite layer, improves the charge transfer path, reduces the non-radiative recombination phenomenon, significantly improves the VOC of the perovskite solar cell, improves the photoelectric conversion efficiency (PCE) of the perovskite solar cell, can output a higher voltage under illumination conditions, enhances the power output of the perovskite solar cell, and enhances the long-term stability of the perovskite solar cell.

[0039] In the present invention, the surfactant may be one or more selected from organic substances containing phosphate groups and organic substances containing phosphoric acid choline groups; preferably, the organic substance containing phosphate groups may be selected from octadecyl phosphate, dodecyl phosphate, nonylphenol polyoxyethylene phosphate, octyl polyoxyethylene phosphate, polyoxyethylene sorbitan monostearate phosphate, polyoxyethylene fatty alcohol phosphate, lecithin phosphate, triethanolamine phosphate and triethyl phosphate; the organic substance containing phosphoric acid choline group may be selected from distearoyl glycerophosphocholine, stearoyl glycerophosphocholine, palmitoyl glycerophosphocholine, myristoyl glycerophosphocholine, lauryl phosphoric acid choline, dodecyl phosphoric acid choline, tetradecyl phosphoric acid choline, hexadecyl phosphoric acid choline, behenyl phosphoric acid choline, dilauryl dimethyl phosphoric acid choline and glycerophosphocholine. In the present invention, the use of the above-mentioned surfactant can effectively improve the photovoltaic performance and long-term stability of perovskite solar cells.

[0040] In the present invention, the self-assembling molecular material can be one or more selected from [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz).

[0041] In the present invention, the mass ratio of the self-assembling molecular material and the surfactant can be 1: (0.001-100), preferably 1: (0.001-1); for example, 1: 0.001, 1: 0.002, 1: 0.005, 1: 0.01, 1: 0.02, 1: 0.05, 1: 0.07, 1: 0.1, 1: 0.2, 1: 0.5, 1: 0.7, 1: 1. In the present invention, the mass ratio of the self-assembling molecular material and the surfactant is controlled within the above preferred range, which is beneficial to improving the short-circuit current density, open-circuit voltage, fill factor, photoelectric conversion efficiency and long-term stability of the perovskite solar cell.

[0042] In the present invention, the thickness of the NiOx layer can be 1-100nm, such as 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. The thickness of the self-assembled molecular layer can be 1-20nmnm, such as 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm. The thickness of the hole transport layer can be 2-120nm, such as 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm.

[0043] The method for preparing a hole transport layer provided by the present invention comprises: coating a self-assembled molecular layer precursor liquid on the surface of a NiOx layer, and obtaining a self-assembled molecular layer after annealing; the self-assembled monomolecular layer precursor liquid comprises a self-assembled molecular material, a surfactant and a solvent. The present invention ensures the uniform distribution and good wettability of the surfactant by adding a surfactant to the self-assembled molecular layer precursor liquid, and improves the interface characteristics between NiOx and the perovskite layer; improves the surface wettability of the NiOx layer by modification, ensures the uniform distribution of the self-assembled molecular layer on NiOx, thereby reducing interface defects and improving the charge transfer path; the modified interface reduces the non-radiative recombination phenomenon, significantly improves the VOC of the perovskite solar cell, and enhances the long-term stability of the perovskite solar cell by optimizing the interface structure.

[0044] In the process of preparing the hole transport layer of the present invention, the deposition method of the NiOx layer can be physical vapor deposition (PVD), spin coating, blade coating or slit coating.

[0045] In the process of preparing the hole transport layer of the present invention, the annealing temperature can be 100-150° C., for example, 100° C., 110° C., 120° C., 130° C., 140° C., 150° C. The annealing time can be 5-20 min, for example, 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, 17 min, 19 min, 20 min.

[0046] In the process of preparing the hole transport layer of the present invention, in the self-assembled molecular layer precursor solution, the solvent can be one or more selected from N,N-dimethylformamide (DMF), ethanol (EtOH) and isopropyl alcohol (IPA). In the self-assembled molecular layer precursor solution, the concentration of the self-assembled molecular material can be 0.1-10 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, 3.0 mg / mL, 4.0 mg / mL, 5.0 mg / mL, 6.0 mg / mL, 7.0 mg / mL, 8.0 mg / mL, 9.0 mg / mL, 10.0 mg / mL. In the self-assembled molecular layer precursor solution, the concentration of the surfactant can be 0.1-10 mg / mL, preferably 0.1-1 mg / mL, such as 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL. In the present invention, controlling the concentration of the surfactant within the above preferred range is beneficial to improving the short-circuit current density, open-circuit voltage, fill factor, photoelectric conversion efficiency and long-term stability of the perovskite solar cell.

[0047] In the process of preparing the hole transport layer of the present invention, the coating mode of the self-assembled molecular layer precursor solution can be spin coating, scraping coating or slit coating. When the method of spin coating is adopted, the spin coating speed can be 3000-6000 revolutions per second, such as 3000 revolutions per second, 3500 revolutions per second, 4000 revolutions per second, 4500 revolutions per second, 5000 revolutions per second, 5500 revolutions per second, 6000 revolutions per second. When the method of spin coating is adopted, the acceleration can be 1000-5000 revolutions per second, such as 1000 revolutions per second, 2000 revolutions per second, 3000 revolutions per second, 4000 revolutions per second, 5000 revolutions per second. When the method of spin coating is adopted, the spin coating time can be 20-60s, such as 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s. When the scraper coating method is adopted, the coating speed can be 5-20 mm / s, such as 5 mm / s, 7 mm / s, 9 mm / s, 11 mm / s, 13 mm / s, 15 mm / s, 17 mm / s, 19 mm / s, 20 mm / s. When the slit coating method is adopted, the coating speed can be 5-20 mm / s, such as 5 mm / s, 7 mm / s, 9 mm / s, 11 mm / s, 13 mm / s, 15 mm / s, 17 mm / s, 19 mm / s, 20 mm / s.

[0048] The perovskite solar cell of the present invention may further include a perovskite light absorbing layer on the surface of the self-assembled molecular layer of the hole transport layer.

[0049] The perovskite solar cell of the present invention may be a single-junction perovskite solar cell or a stacked perovskite solar cell.

[0050] In some embodiments, the perovskite solar cell includes a conductive substrate, a hole transport layer, a perovskite light absorbing layer, an electron transport layer and a back electrode in sequence from the thickness direction, and the hole transport layer includes a NiOx layer and a self-assembled molecular layer in sequence from the thickness direction.

[0051] In the present invention, the conductive substrate can be a flexible substrate or a rigid substrate; preferably, the rigid substrate can be indium tin oxide (ITO) transparent conductive glass, fluorine-doped tin oxide (FTO) transparent conductive glass, tungsten-doped indium oxide (IWO) transparent conductive glass and aluminum-doped zinc oxide (AZO) transparent conductive glass.

[0052] In the present invention, the chemical formula of the perovskite structure material can be ABX3, A can be a monovalent cation, which can be one or more selected from methylamine (MA), formamidine (FA), acetamidine, cesium and rubidium; B can be a divalent metal cation, which can be one or more selected from lead, tin, copper and germanium; X can be a monovalent anion, which can be one or more selected from F - ,I - Br - , Cl - 、BF4 - PF6 - and SCN - One or more of .

[0053] In the present invention, the material of the electron transport layer can be one or more selected from [6,6]-phenyl-C71-butyric acid isomethyl ester (PCBM), SnO2, ZnO2, Al2O3, C60 and indene-C60 bisadduct (ICBA).

[0054] In the present invention, the back electrode can be a metal electrode or a transparent electrode. Preferably, the metal electrode material can be Ag, Au or Cu; the transparent electrode material can be indium tin oxide (ITO), fluorine-doped tin oxide (FTO) or zinc-doped zinc oxide (IZO).

[0055] In the present invention, the thickness of the perovskite light absorbing layer can be 200-700nm, for example, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm.

[0056] In the present invention, the thickness of the electron transport layer can be 10-50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.

[0057] In the present invention, the thickness of the back electrode may be 50-200 nm, for example, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, or 200 nm.

[0058] The present invention can provide a method for preparing the perovskite solar cell of the present invention, the method comprising the following steps:

[0059] (1) depositing a NiOx layer on the surface of a conductive substrate and then depositing a self-assembled molecular layer to obtain a hole transport layer;

[0060] (2) depositing a perovskite light absorbing layer on the surface of the hole transport layer;

[0061] (3) depositing an electron transport layer on the surface of the perovskite light absorbing layer;

[0062] (4) Depositing a back electrode on the surface of the electron transport layer to obtain a perovskite solar cell.

[0063] In step (2), a perovskite precursor solution is prepared using raw materials of a perovskite structured material, the perovskite layer precursor solution is coated on the surface of the hole transport layer, and the perovskite light absorbing layer is obtained after annealing.

[0064] In step (2), the coating method can be spin coating, blade coating or slit coating.

[0065] In step (2), the annealing method can be one-step annealing or two-step annealing; preferably, one-step annealing is a single annealing; and two-step annealing is a primary annealing and a secondary annealing in sequence.

[0066] In step (2), in the perovskite layer precursor solution, the concentration of divalent metal cations in the theoretically generated perovskite structure material can be 0.2-2 mol / L, for example, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L.

[0067] In step (2), the solvent may be one or more selected from dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), acetonitrile (ACN), N-methylpyrrolidone (NMP), 2-methoxyethanol and γ-butyrolactone.

[0068] In step (2), during the one-step annealing process, the annealing temperature of the single annealing can be 60-180°C, for example, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C.

[0069] In step (2), during the one-step annealing process, the annealing time of the single annealing can be 1-80 min, for example, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min.

[0070] In step (2), during the two-step annealing process, the annealing temperature of the secondary annealing can be 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C.

[0071] In step (2), during the two-step annealing process, the annealing time of the secondary annealing can be 1-30 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min.

[0072] In step (2), during the two-step annealing process, the annealing temperature of the secondary annealing can be 80-180°C, for example, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C.

[0073] In step (2), during the two-step annealing process, the annealing time of the secondary annealing can be 1-60 min, for example, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min.

[0074] In step (3), the electron transport layer may be deposited by thermal evaporation.

[0075] In step (4), the back electrode can be deposited by thermal evaporation or physical vapor deposition.

[0076] Compared with the prior art, the present invention has the following beneficial effects:

[0077] (1) The method of adding a surfactant to the SAM of the present invention does not require additional perovskite buried interface passivation treatment, which reduces the preparation process, simplifies the production steps, makes the operation process simpler, reduces the dependence on high-cost self-assembly molecules and complex processing techniques, makes the production process more efficient, and reduces the dependence on high-end materials, so that the overall production cost is controlled and the economic efficiency of the technology is improved. Compared with other complex interface modification methods, it is more direct and efficient to implement, and is easier to mass produce and commercialize;

[0078] (2) The method of adding a surfactant to the SAM of the present invention has better wettability of the modified solution, so that the self-assembled molecules can form a uniform and stable modified layer on the NiOx layer, thereby improving the wettability and uniformity of the interface, effectively reducing interface defects, and facilitating large-area preparation;

[0079] (3) The present invention reduces the non-radiative recombination phenomenon by optimizing the interface, thereby improving the VOC of the battery. The open circuit voltage is one of the important indicators for measuring the performance of solar cells. Improving the VOC can directly improve the photoelectric conversion efficiency of solar cells, so that the battery can output a higher voltage under light conditions, thereby enhancing the power output of the battery;

[0080] (4) The present invention improves the stability of the device under long-term illumination and environmental conditions by optimizing the interface and improving the interaction between layers, thereby reducing performance degradation and device failure caused by environmental factors;

[0081] (5) The present invention adjusts the type and concentration of the surfactant to quickly optimize the wettability and uniformity of the interface, which is convenient for adjustment and control in actual large-scale production;

[0082] (6) The present invention has good adaptability and is not only suitable for specific types of perovskite materials and hole transport layers, but also can adapt to different perovskite solar cell systems, and has strong versatility and flexibility. Different surfactants can be selected according to specific application requirements to achieve targeted optimization and improve the battery performance under different material systems.

[0083] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0084] Example 1

[0085] Preparation of this example Figure 1 The perovskite solar cell shown in the figure has the following specific steps:

[0086] Preparation of self-assembled molecular layer precursor solution: Me-4PACz and glycerophosphocholine were dissolved in ethanol to prepare a self-assembled molecular layer precursor solution, wherein the concentration of Me-4PACz was 0.5 mg / mL and the concentration of glycerophosphocholine was 0.1 mg / mL;

[0087] Preparation of perovskite precursor solution: The raw material powders of three perovskite structural materials, FAI, PbI2, and CsI, and the additive MACl (methylammonium chloride) with a molar weight of 10% of PbI2 were mixed, and added into 1 mL of DMF and NMP with a volume ratio of 4:1 to dissolve, and 1.5 mol / L of solute was obtained, which was the theoretically generated Cs 0.1 FA 0.9 Perovskite precursor solution of PbI3;

[0088] (1) Conductive substrate pretreatment: The FTO glass is laser-scribed by P1, then cleaned and dried with nitrogen to obtain a clean conductive substrate;

[0089] (2) Preparation of hole transport layer: NiOx was sputtered on a conductive substrate by PVD method to obtain a NiOx layer with a thickness of 15 nm; the self-assembled molecular layer precursor prepared above was spin-coated and deposited on the surface of the NiOx layer by slit coating method to obtain a self-assembled molecular layer with a thickness of 5 nm. In the slit coating process, the coating speed was 10 mm / s, the ambient temperature was 25±5°C, and the ambient humidity was 20±5% RH. After slit coating, the layer was annealed on a hot plate at 130°C for 10 min to obtain a hole transport layer composed of the NiOx layer and the self-assembled molecular layer;

[0090] (3) Preparation of perovskite light-absorbing layer: In an air environment, the above-prepared perovskite precursor solution is coated on the hole transport layer through slit coating. In the slit coating process, the coating height is 100 μm, the coating liquid output is set to 300 μL, the plunger pump injection speed is 1 μL / s, the platform movement speed is adjusted to 10 mm / s, the preparation environment temperature is 25±5°C, and the environment humidity is 20±5% RH; after the coating is completed to form a perovskite wet film, the wet film is immediately moved to a vacuum extraction chamber for vacuum drying, the vacuum pressure is 10 Pa, the vacuum time is 30 s, and the dried film is placed on a hot stage set at a temperature of 130°C for annealing for 30 min to obtain a perovskite light-absorbing layer with a thickness of 500 nm;

[0091] (4) Preparation of electron transport layer: A C60 layer with a thickness of 30 nm and a SnO2 layer with a thickness of 20 nm are sequentially deposited on the perovskite light absorption layer by vacuum evaporation. The C60 layer and the SnO2 layer together constitute the electron transport layer. After the electron transport layer is prepared, laser P2 scribing is performed immediately;

[0092] (5) Preparation of back electrode: Cu with a thickness of 120 nm was evaporated on the electron transport layer by vacuum evaporation to obtain a back electrode, and laser P3 scribing and P4 edge cleaning were performed to obtain a perovskite solar cell module.

[0093] Example 2

[0094] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the self-assembled molecular layer precursor solution of this embodiment is triethyl phosphate.

[0095] Example 3

[0096] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the precursor solution of the self-assembled molecular layer of this embodiment is stearoylglycerophosphocholine.

[0097] Example 4

[0098] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the precursor solution of the self-assembled molecular layer of this embodiment is dodecylphosphocholine.

[0099] Example 5

[0100] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the self-assembled molecular layer precursor solution of this embodiment is nonylphenol polyoxyethylene phosphate.

[0101] Example 6

[0102] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the self-assembled molecular layer precursor solution of this embodiment is triethanolamine phosphate.

[0103] Example 7

[0104] The other conditions of this embodiment are the same as those of embodiment 1, except that the surfactant in the self-assembled molecular layer precursor solution of this embodiment is dodecyl phosphate.

[0105] Comparative Example 1

[0106] The other conditions of this comparative example are the same as those of Example 1, except that the self-assembled molecular layer precursor solution of this comparative example does not contain a surfactant.

[0107] Test Case

[0108] Initial performance test of perovskite solar cells: At 25°C and AM 1.5G standard solar spectrum, using a solar simulator, the voltage range was set to 0.2-12V, the current output of the perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 49cm 2 , the incident light power (Pin) is 100mW / cm 2 The characteristic curve at this time is the characteristic curve of initial performance, and the initial performance (initial open circuit voltage, initial short circuit current density, initial fill factor and initial photoelectric conversion efficiency) of the perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 are obtained based on the characteristic curve of initial performance.

[0109] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.

[0110] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.

[0111] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.

[0112] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.

[0113] Aging performance test of perovskite solar cells: The perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 were aged for 48 h at 25°C and AM 1.5G in an open circuit. A solar simulator was used to set the voltage range to 0.2-12V. The current output of the perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted. The cell surface area was 49 cm 2 , the incident light power (Pin) is 100mW / cm 2 The characteristic curve at this time is the characteristic curve of aging performance, and the aging performance (open circuit voltage after aging, short circuit current density after aging, fill factor after aging, and photoelectric conversion efficiency after aging) of the perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 is obtained from the characteristic curve of aging performance.

[0114] Efficiency ratio of perovskite solar cells: Efficiency ratio = initial photoelectric conversion efficiency / photoelectric conversion efficiency after aging × 100%.

[0115] The test results of the initial performance, aging performance and efficiency ratio of the perovskite solar cells prepared in Examples 1-7 and Comparative Example 1 are shown in Table 1.

[0116] Table 1: Initial performance, aging performance and efficiency ratio of perovskite solar cells prepared in Examples 1-7 and Comparative Example 1

[0117]

[0118]

[0119] It can be seen from Table 1 that compared with the perovskite solar cell prepared in Comparative Example 1 without a self-assembled molecular layer having a surfactant, the initial performance, aging performance and efficiency ratio of the perovskite solar cell with a self-assembled molecular layer having a surfactant prepared in Example 7 are all improved, which means that the perovskite solar cell prepared by the present invention has excellent device performance and stability.

Claims

1. A hole transport layer, characterized in that: The hole transport layer comprises a NiOx layer and a self-assembled molecular layer, and the self-assembled molecular layer comprises a self-assembled molecular material and a surfactant.

2. The hole transport layer according to claim 1, characterized in that The hole transport layer has one or more of the following characteristics: The surfactant is selected from one or more of organic substances containing phosphate groups and organic substances containing phosphorylcholine groups; The self-assembling molecular material is selected from one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid; The mass ratio of the self-assembling molecular material to the surfactant is 1:(0.001-100); The thickness of the NiOx layer is 1-100 nm; The thickness of the self-assembled molecular layer is 1-20 nm; The thickness of the hole transport layer is 2-120 nm.

3. The hole transport layer according to claim 2, characterized in that The organic matter containing phosphate groups is selected from one or more of octadecyl phosphate, dodecyl phosphate, nonylphenol polyoxyethylene phosphate, octyl polyoxyethylene phosphate, polyoxyethylene sorbitan monostearate phosphate, polyoxyethylene fatty alcohol phosphate, lecithin phosphate, triethanolamine phosphate and triethyl phosphate; and / or The organic matter containing a phosphorylcholine group is selected from one or more of distearoylglycerophosphocholine, stearoylglycerophosphocholine, palmitoylglycerophosphocholine, myristoylglycerophosphocholine, laurylphosphocholine, dodecylphosphocholine, tetradecylphosphocholine, hexadecylphosphocholine, behenylphosphocholine, dilauryl dimethylphosphocholine and glycerophosphocholine.

4. A method for preparing a hole transport layer according to any one of claims 1 to 3, characterized in that: The method comprises: coating a self-assembling molecular layer precursor solution on the surface of a NiOx layer, and obtaining the self-assembling molecular layer through annealing; the self-assembling molecular layer precursor solution comprises a self-assembling molecular material, a surfactant and a solvent.

5. The method according to claim 4, characterized in that The NiOx layer is prepared by physical vapor deposition, spin coating, doctor blade coating or slit coating.

6. The method according to claim 4, characterized in that The method has one or more of the following features: Annealing temperature is 100-150°C; Annealing time is 5-20min; The self-assembled molecular layer precursor solution is coated by spin coating, blade coating or slit coating; The solvent is selected from one or more of N,N-dimethylformamide, ethanol and isopropanol; In the self-assembled molecular layer precursor solution, the concentration of the self-assembled molecular material is 0.1-10 mg / mL; In the self-assembled molecular layer precursor solution, the concentration of the surfactant is 0.1-10 mg / mL.

7. The method according to claim 6, characterized in that The method has one or more of the following features: When the spin coating method is adopted, the spin coating speed is 3000-6000 revolutions per second; When the spin coating method is adopted, the spin coating acceleration is 1000-5000 revolutions per second; When the spin coating method is adopted, the spin coating time is 20-60s; When using the scraper coating method, the coating speed is 5-20mm / s; When the slit coating method is adopted, the coating speed is 5-20 mm / s.

8. A perovskite solar cell comprising the hole transport layer according to any one of claims 1 to 3.

9. The perovskite solar cell according to claim 8, characterized in that The perovskite solar cell further comprises a perovskite light absorbing layer on the surface of the self-assembled molecular layer of the hole transport layer.

10. The perovskite solar cell according to claim 9, characterized in that: The perovskite light-absorbing layer comprises a perovskite structure material, the chemical formula of the perovskite structure material is ABX3, A is a monovalent cation selected from one or more of methylamine, formamidine, acetamidine, cesium and rubidium; B is a divalent metal cation selected from one or more of lead, tin, copper and germanium; X is a monovalent anion selected from F - ,I - Br - , Cl - 、BF4 - PF6 - and SCN - One or more of .

Citation Information

Cited By

  • Perovskite battery with self-assembled monomolecular layer and preparation method thereof

    CN119923068A

  • Perovskite solar cell, preparation method thereof and power utilization device

    CN122094291A